Precise control of the site selectivity in ruthenium-catalyzed C–H bond amidations using cyclic amides as powerful directing groups. Issue 1 (22nd November 2022) - Yuan, Yu-Chao; Lu, Qiu-Li; Zhu, Xiao-Tong; Posada-Pérez, Sergio; Solà, Miquel; Poater, Albert; Roisnel, Thierry; Gramage-Doria, Rafael
Abstract : A ruthenium-catalyzed C–H amidation using cyclic amides as directing groups features broad functional group tolerance. Mechanistic studies supported by DFT calculations highlight the relevance of six-membered ruthenacycles in the catalytic cycle. Abstract : Selective C–H functionalizations aiming at the formation of new C–N bonds is of paramount importance in the context of step- and atom-economy methodologies in organic synthesis. Although the implementation of noble metal catalysts is prevalent, more benign cobalt pre-catalysts have recently appeared to be promising. However, they sometimes feature selectivity issues that limit their applicability in late-stage functionalization. Herein, we report on a highly reactive ruthenium-based catalytic system displaying excellent levels of mono-, regio- and site-selectivity by exploiting a series of biologically-relevant cyclic amides as weak directing groups. The use of dioxazolone derivatives as amidating reagents overcomes the issues encountered in the use of unstable azide derivatives for such transformations and it enables us to perform these reactions under very mild reaction conditions (air, 40 °C). Moreover, a combination of deuteration experiments and a comparative study with different types of directing groups highlights the relevance of weak amide directing groups for enabling the formation of six-membered cycloruthenate intermediates in the key elementary steps of the catalytic cycle. In addition, DFT computational calculations were carried out for the first time for studying ruthenium-catalyzed C–N bond-forming processes via C–H activation assisted by weak directing groups, thereby elucidating the origin of the regio- and site-selectivity.